DESIGN OF PADIBON APPLICATION AS E-MARKETPLACE FOR MSME ACTIVITIES IN CIREBON CITY USING THE LARAVEL FRAMEWORK - Ilwan Syafrinal; Chairun Nas; Nursaka Putra (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: The government's effort to improve the community's economy is to give birth to Micro, Small and Medium Enterprises (MSMEs) in the midst of the community. The people of Cirebon city are people who are starting of being a productive society, so that MSMEs are born in the city of Cirebon. However, limited land for the process of buying and selling and marketing products has, in MSMEs being run by the community often resulting in bankruptcy due to market competitiveness. So to overcome this problem, we need a media that can distribute the results of MSME products for the people of the city of Cirebon without having to have land to sell products. This research was conducted of building an E-Marketplace (Digital Market) system that is used by the people of the city of Cirebon to promote, sell and buy the products of the Cirebon city community's MSME products online based on a Website . Apart from that, with the E-Marketplace, it can help MSMEs in the city of Cirebon continue to run their business during this pandemic even though there are Community Activity Restrictions (PPKM). In this study, the research method applied is the System Development Life Circle, where the method includes the process of data collection and analysis, system design, system development and system implementation and system testing. The results of this application design will be named Padibon . So with this Padibon application, MSME actors in marketing their products, and consumers can buy MSME products anywhere and anytime.            Keywords: E-Marketplace; Frameworks; MSMEs; SDLC Abstrak: Usaha pemerintah dalam meningkatan perekonomian masyarakat adalah dengan melahirkan Usaha Mikro Kecil Menengah (UMKM) didalam lingkungan masyarakat. Masyarakat kota Cirebon merupakan masyarakat yang mulai menyadari pentingnya menjadi masyarakat yang produktif. Namun keterbatasan lahan untuk proses jual beli dan pemasaran produk mengakibatkan UMKM yang di jalankan oleh masyarakat seringkali mengakibatkan kebangkrutan karena daya saing pasar. Maka untuk mengatasi masalah tersebut, diperlukan sebuah media yang dapat menyalurkan hasil produk UMKM masyarakat kota Cirebon tanpa harus adanya lahan tempat menjual produk. Penelitian dilakukan  untuk membangun sebuah sistem E- Marketplace (Pasar Digital) yang digunakan oleh masyarakat kota Cirebon untuk mempromosikan, menjual dan membeli hasil-hasil produk UMKM masyarakat kota Cirebon secara online berbasis Website. Selain dari itu, dengan adanya aplikasi ini  maka dapat membantu UMKM masyarakat kota Cirebon tetap menjalankan usahanya di masa pandemi ini walaupun terdapat Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM). Pada penelitian ini, metode yang diterapkan adalah System Development Life Circle, dimana metode tersebut meliputi proses pengumpulan dan analisis data, design system, development system dan implementasi sistem serta pengujian sistem. Hasil dari perancangan aplikasi ini adakan diberi nama Padibon. Maka dengan aplikasi Padibon ini, pelaku UMKM dapat memasarkan hasil produknya, dan konsumen bisa membeli produk UMKM dimanapun dan kapanpun. Kata kunci: E-Marketplace; Framework; SDLC; UMKM